A glycoconjugate antigen based on the recognition motif of a broadly neutralizing human immunodeficiency virus antibody, 2G12, is immunogenic but elicits antibodies unable to bind to the self glycans of gp120. - Astronomo, R; Lee, H; Scanlan, C; Pantophlet, R; Huang, C; Wilson, I; Blixt, O; Dwek, R; Wong, C; Burton, DR (2008)
The glycan shield of human immunodeficiency virus type 1 (HIV-1) gp120 contributes to viral evasion from humoral immune responses. However, the shield is recognized by the HIV-1 broadly neutralizing antibody (Ab), 2G12, at a relatively conserved cluster of oligomannose glycans. The discovery of 2G12 raises the possibility that a carbohydrate immunogen may be developed that could elicit 2G12-like neutralizing Abs and contribute to an AIDS vaccine. We have previously dissected the fine specificity of 2G12 and reported that the synthetic tetramannoside (Man(4)) that corresponds to the D1 arm of Man(9)GlcNAc(2) inhibits 2G12 binding to gp120 as efficiently as Man(9)GlcNAc(2) itself, indicating the potential use of Man(4) as a building block for creating immunogens. Here, we describe the development of neoglycoconjugates displaying variable copy numbers of Man(4) on bovine serum albumin (BSA) molecules by conjugation to Lys residues. The increased valency enhances the apparent affinity of 2G12 for Man(4) up to a limit which is achieved at approximately 10 copies per BSA molecule, beyond which no further enhancement is observed. Immunization of rabbits with BSA-(Man(4))(14) elicits significant serum Ab titers to Man(4). However, these Abs are unable to bind gp120. Further analysis reveals that the elicited Abs bind a variety of unbranched and, to a lesser extent, branched Man(9) derivatives but not natural N-linked oligomannose containing the chitobiose core. These results suggest that Abs can be readily elicited against the D1 arm; however, potential differences in the presentation of Man(4) on neoglycoconjugates, compared to glycoproteins, poses challenges for eliciting anti-mannose Abs capable of cross-reacting with gp120 and HIV-1.